CINEMATIC ARCHITECTURE APPROACH IN I&L HOUSE - Rafii Putra Wedaswara ; Yenny Gunawan (Riset Arsitektur (RISA), 2018)
Abstract- AMI is an architecture movement, lead by 10 young Indonesian architects, is not satisfy with Indonesian architecture scene at that time, which they called “less interesting”, “monotone” and “lack of character”. AMI is considered to be against of mainstream architecture at that time, identified by having their own idealism, signature, and style. Andra Matin as one of the initiators of the movement, offering a characteristic architecture and not monotonous as the spirit of design direction. Quoting from David Hutama, a curator from architecture media rooang.com, by having a review on Andra Matin design: His works giving an impression of connectedness from one level to another level, making it have an own unique cinematic style caused by an emotional way of aesthetical response through sequence of an user. And many of his works depict minimalist stripes with geometry structure. The goal of this research is to identify a perception of space on one of Andra Matin works, I&L House.The methodological research used on this research is a descriptive-qualitative through cimematic architecture approach. Data types that used for an analysis is mental space element, material space, and lived space. The data is obtained from three instrument of gathering data, such as observation, interview, and questionnaire. Analitic technique is built from quantitative analysis and qualitative analysis, from comparing the user analysis report and perceotion data which carried by respondent.The summary of this research is to define a mental space and material space on the object. The most significant of mental space element and space material giving an influence on shaped space perception such as masculine, directing and exposed, in a lived space element of I&L house user such as material, shape, light, and sound. In the end, the writer use film as tool for visualizing the summary of this research. Key Words: cinematic architecture, Andra Matin, i&l house